Understanding ferroelectricity in sputtered aluminum nitride thin films on silicon - Vamshi Kiran Gogi; Christopher Chae; Abhijeet Barua; Jinwoo Hwang; Rashmi Jha (APL Materials)
We report ferroelectric switching at room temperature in sub-100 nm aluminum nitride thin films deposited using radio frequency magnetron sputtering in a metal–insulator–metal configuration. The film microstructures were investigated using transmission electron microscopy. Ferroelectric characteristics have been investigated through dynamic hysteresis mode and positive-up-negative-down techniques that underscore contributions from leakage current showing the overestimated remnant polarization (Pr > 100 μC/cm2) values. True ferroelectric switching characterization shows a complete polarization reversal with a Pr of ∼90 μC/cm2. The interface trap density (Dit) at the AlN/Si interface in the metal–insulator–semiconductor configuration is estimated to be 6.91 × 1013 cm−2 eV−1 using conductance spectroscopy, indicating flatband voltage (∆Vfb) shifts dominated by charge trapping.